2008
DOI: 10.1002/dvdy.21562
|View full text |Cite
|
Sign up to set email alerts
|

The germ plasm component vasa allows tracing of the interstitial stem cells in the cnidarian Hydractinia echinata

Abstract: Germ cells in hydrozoans arise lifelong from multipotent interstitial stem cells. To discover if a true germline-soma segregation exists in these species, we studied gametogenesis in Hydractinia echinata using in situ hybridization and immunohistochemistry for the germ cell marker Vasa. We could show that Hevas is a zygotic transcript, present in embryos from the gastrula stage onward. In the planula larva, Hevas is expressed in the interstitial stem cells located in the endoderm. During metamorphosis, Hevas-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 46 publications
(83 reference statements)
6
56
0
Order By: Relevance
“…In several model organisms, such as Caenorhabditis elegans, Drosophila melanogaster and Xenopus laevis, primordial germ cells are specified and set aside very early in embryogenesis initiated by maternal signals. By contrast, in Hydractinia, adult stem cells preserve pluripotency and thus the capability to give rise to germ cells throughout life, probably enabled by Oct4-like POU factors , by Vasa (Rebscher et al, 2008), Piwi (called Cniwi in Podocoryne carnea; Seipel et al, 2004b; this report, Table 1), Nanos and Myc2 (this report, Table 1), like in many bilaterians (Extavour et al, 2005). Sex determination is upstream of germ cell specification, and is stem cell autonomous rather than being induced by signals from somatic tissues.…”
Section: Specification Of Germ Cells and Sex Determinationmentioning
confidence: 97%
See 2 more Smart Citations
“…In several model organisms, such as Caenorhabditis elegans, Drosophila melanogaster and Xenopus laevis, primordial germ cells are specified and set aside very early in embryogenesis initiated by maternal signals. By contrast, in Hydractinia, adult stem cells preserve pluripotency and thus the capability to give rise to germ cells throughout life, probably enabled by Oct4-like POU factors , by Vasa (Rebscher et al, 2008), Piwi (called Cniwi in Podocoryne carnea; Seipel et al, 2004b; this report, Table 1), Nanos and Myc2 (this report, Table 1), like in many bilaterians (Extavour et al, 2005). Sex determination is upstream of germ cell specification, and is stem cell autonomous rather than being induced by signals from somatic tissues.…”
Section: Specification Of Germ Cells and Sex Determinationmentioning
confidence: 97%
“…Most observations and investigations on stem cells in Cnidaria have been made in Hydra (reviewed by Bode, 1996;Bosch, 2007Bosch, , 2009Bosch et al, 2010;Watanabe et al, 2009;David 2012;Hobmayer 2012 in this issue) and in Hydractinia (Weismann, 1883;Hoffmann and Kroiher, 2001;Müller et al, 2004a;Teo et al, 2006;Rebscher et al, 2008;Künzel et al, 2010;Millane et al, 2011). The stem cells are also known as interstitial cells (i-cells) as they reside in interstitial spaces at the bases of the epithelia (Weismann, 1883).…”
Section: Identification and Characterization Of I-cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that CEL expression commences just after oogenesis has started in germ cells before entering the gonads. It is the same region of the sexual polyp where i-cells stop expressing Vasa, a stem cell marker in Hydractinia, before they enter the gonad and complete oogenesis (Rebscher et al, 2008). Possibly, this is also the stage where i-cells lose pluripotency to become committed to gamete differentiation.…”
Section: Analysis Of Cel Spatial Expression By In Situ Hybridizationmentioning
confidence: 99%
“…The expression of nanos-, vasa-and PL10-related genes (Mochizuki et al, 2000(Mochizuki et al, , 2001 was demonstrated for the adult interstitial and germline cells for the hydrozoan Hydra magnipapillata (Cnidaria); piwi-like expression was found in germline and stem cells of the jellyfish Podocoryne carnea (Seipel et al, 2004). vasa-like gene expresses in interstitial stem cells of Hydractinia echinata (Rebscher et al, 2008). Piwi/Ago, Pumilio, PCNA were revealed in the hydrozoan Hydra magnipapillata and the anthozoan Nematostella vectensis, whereas orthologues of Oct4 and Nanog were not found (Watanabe et al, 2009).…”
Section: Molecular Signature In Pluripotent Gametogenic Stem Cellsmentioning
confidence: 99%